Pengaruh Layanan Jasa Titip Online dan Kualitas Produk terhadap Pendapatan pada Toko Fashion di Kampoeng Collection - Silvia Janela Br Tarigan; Yuni Syahputri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Kampoeng Collection is a local fashion store operating in Pancur Batu District, Deli Serdang Regency, which serves offline fashion product sales. The phenomenon in this study arose due to a consecutive decline in revenue from 2022 to 2024. The decline in revenue is thought to be influenced by the increasing use of online consignment services and consumer perceptions of product quality compared to other products, especially imported products. This study used a quantitative research method with an associative approach. Data were collected by distributing questionnaires to 68 respondents who had shopped offline at Kampoeng Collection Fashion Store. The data analysis method used multiple linear regression with t-test, F-test, and coefficient of determination using the SPSS program. The results showed that the online consignment service variable had a positive and significant effect on revenue with a t-value of 3.904 and a significance value <0.05. The product quality variable also had a positive and significant effect on revenue with a t-value of 2.874 and a significance value of 0.005. Simultaneously, online consignment services and product quality had a positive and significant effect on revenue, with a calculated F-value of 16.020, greater than the F-table value of 3.09 and a significance value <0.05. The coefficient of determination test showed an adjusted R-square value of 0.310, indicating that 31.0% of revenue variation can be explained by online consignment services and product quality, while the remaining 69.0% is influenced by other variables outside this study.